Axiolinguistic Characteristics of Poverty in the Ukrainian Language and Linguistic Culture - Iarotska, Galyna (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2024)
The verbal objectification of subjective features and society's assessment of the economic status of a certain segment of the population are of interest in this linguistic and cultural study, which aims to diachronically and synchronously analyze the conceptualization of poverty in Ukrainian linguistic culture and in the language consciousness. The peculiarity of the process of forming the economic identification of a person is that there are objective signs of a person's property status that have a pronounced national, socio-economic, cultural and regional character. These objective features are also conditioned by systemic, linguistic and linguistic-cultural factors that have a significant impact on the value level of collective and individual economic consciousness. We also focused on the study of the perception and interpretation of the concept of "poverty" by modern Ukrainians. To do this, we used the methods of questionnaires and an association experiment. First, we provided the definition of "poverty" by economic science and sociology, considering also the concepts of "psychology of poverty" and economic identification; second, we analyzed the concept of "poverty" in the historical perspective on the basis of dictionary information by creating a nominative space of the concept; third, we turned to experimental methods, namely, an association experiment and a questionnaire survey. The results showed that modern native speakers no longer perceive poverty as a manifestation of evil fate or God's punishment, but as a result, on the one hand, of their own inability to earn enough money, or, on the other hand, as a consequence of economic crises and hardships that cause a person's material condition to deteriorate. A person who is poor or in need has to take responsibility for himself or herself and not expect help from other people. The perception and interpretation of concepts from the nominal space of poverty has certain differences compared to the interpretation by historical dictionaries. Thus, a poor person cannot even count on sympathy, because his poverty is the result of his inaction, laziness, etc.